2017
DOI: 10.1080/14760584.2017.1355245
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of mRNA-based vaccines

Abstract: The present review summarizes the growing body of work defining the mechanisms of action of this exciting new vaccine technology that should allow rational approaches in the design of next generation mRNA vaccines. Areas covered: Bio-distribution of mRNA, localization of antigen production, role of the innate immunity, priming of the adaptive immune response, route of administration and effects of mRNA delivery systems. Expert commentary: In the last few years, the development of RNA vaccines had a fast growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
151
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 183 publications
(157 citation statements)
references
References 110 publications
1
151
0
5
Order By: Relevance
“…173,181 The resultant RNA, termed replicon, usually contains two different ORFs, with one encoding nonstructural proteins that help RNA capping and replication and the other expressing the antigen that replaces the viral structural protein ( Figure 3B). 163 SAM vaccines have several attractive features, such as extending the duration (approximately 2 months) and magnitude of expression compared to their non-replicating counterparts. However, in order to maintain selfamplifying activity, these RNA replicons are not able to tolerate many of the synthetic nucleotide modifications and sequence alterations.…”
Section: Sam Vaccinesmentioning
confidence: 99%
“…173,181 The resultant RNA, termed replicon, usually contains two different ORFs, with one encoding nonstructural proteins that help RNA capping and replication and the other expressing the antigen that replaces the viral structural protein ( Figure 3B). 163 SAM vaccines have several attractive features, such as extending the duration (approximately 2 months) and magnitude of expression compared to their non-replicating counterparts. However, in order to maintain selfamplifying activity, these RNA replicons are not able to tolerate many of the synthetic nucleotide modifications and sequence alterations.…”
Section: Sam Vaccinesmentioning
confidence: 99%
“…excessive activation can also interfere with antigen expression and adaptive immunity. 61,62 For example, Karikó et al 57 and others 44,[63][64][65][66][67][68][69] have shown that pseudouridine-containing mRNAs reduce activation of Toll-like receptors (TLRs), retinoic acid-inducible gene I (RIG-I), protein kinase R (PKR), and 2 0 -5 0 -oligoadenylate synthetase (OAS), while increasing translational activity, resistance to RNase L-mediated degradation, and in vivo stability. The highest levels of protein production and immunogenicity are observed when nucleoside-modified mRNA is also purified by high-performance liquid chromatography (HPLC) or fast protein liquid chromatography (FPLC), where aberrant double-stranded transcripts are removed.…”
Section: Cell-free Production and Purification Of Mrna Vaccinesmentioning
confidence: 99%
“…Alternatively, we speculate that the lower potency of a highly attenuated or inactivated VEE RNA vaccine could be overcome by further improvement of the synthetic non-viral delivery system, for example, by optimizing CNE specifically for VEEV SAM vaccine or utilizing alternative delivery strategies such as LNPs. 8,10,42,43 On a related note, the attenuated LAV m -CNE vaccine was significantly less immunogenic than the parental LAV-CNE vaccine, whereas LAV m -VRPs was similar to LAV-VRPs. It is possible that the VRP presents glycoproteins authentically to allow for more efficient uptake of the particles as compared to CNE so that both LAV m -VRPs and LAV-VRPs could efficiently launch to induce robust immune responses.…”
Section: Discussionmentioning
confidence: 98%